2004
DOI: 10.1111/j.1600-6143.2004.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Portal Venous Pancreas Graft Drainage on Kidney Graft Outcome in Simultaneous Pancreas-Kidney Recipients Reported to UNOS

Abstract: Clinical data on the potential immunologic impact of portal (PD) vs. systemic (SD) venous pancreas graft drainage on outcome remains controversial.We reviewed the UNOS database to study the effect of PD vs. SD on the incidence of kidney graft rejection and survival in first cadaveric simultaneous pancreas-kidney (SPK) recipients transplanted 1994-2001. We studied three groups: all SPK (n = = 6629, 13% PD) (group I), SPK on tacrolimus (n = = 3563, 17% PD) (group II), and SPK on tacrolimus performed at centers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…No study demonstrated that portal venous drainage increases surgical risk 187,[229][230][231][232][233][234][235] but, on the other hand, no study showed either an immunologic, 199,207,208,229,236 or a metabolic advantage . 233,234,[237][238][239][240][241][242][243][244]…”
Section: Venous Drainagementioning
confidence: 99%
“…No study demonstrated that portal venous drainage increases surgical risk 187,[229][230][231][232][233][234][235] but, on the other hand, no study showed either an immunologic, 199,207,208,229,236 or a metabolic advantage . 233,234,[237][238][239][240][241][242][243][244]…”
Section: Venous Drainagementioning
confidence: 99%
“…Portal venous drainage of pancreas allograft was considered to be able to induce a systemic hyporesponsiveness by portal venous delivery of antigen, although the mechanism by which the liver can induce a state of immunologic hyporesponsiveness following portal antigen presentation are not clearly understood. Several authors (7,8,18) showed lower pancreas and kidney rejection rate sometimes correlated with better graft survival in patients with portal venous drainage of pancreas graft while other authors (10,14,19) and IPTR data did not demonstrate any significant difference in rejection and survival rate between recipients with portal or systemic venous drainage of pancreas allograft. According to the last authors and IPTR we did not show any significant difference between the two groups of patients, although rejection of one or both grafts was surprisingly the most common cause of pancreas and/or kidney loss in recipients with portal venous drainage of pancreas allograft.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies that tackled this subject did so using smaller sample sizes. A study by Troppman et al 17 did use the UNOS data to evaluate this subject, but this was with a smaller sample size, and was published in 2004. Based on current literature, this study comprises a larger sample size and contains more recent information.…”
Section: Discussionmentioning
confidence: 99%